The genetic differentiation of common toads on UK farmland: the effect of straight-line (Euclidean) distance and isolation by barriers in a heterogeneous environment - Macdonald, DW; Salazar, RD; Eynard, SE; Rogers, A; Coles, RS; Montgomery, RA (Society for the Study of Amphibians and Reptiles, 2020)
Genetic differentiation plays an integral role in species persistence. However, it remains challenging to quantify the ways in which the degree of isolation affects animal populations. The Common Toad (Bufo bufo) is a species of conservation concern, particularly in the UK, where populations have undergone large-scale declines. There are two types of isolation that are relevant to toad population persistence. These are: 1) isolation by distance (IBD), where populations that are further apart become more isolated with time; and 2) isolation by barrier (IBB), where the presence of barriers to movement can isolate populations. Both IBB and IBD are relevant to Common Toad survival, and thus conservation, in fragmented landscapes typical of farmlands. We collected Common Toad genetic material from eight different breeding ponds amongst the rural farmland landscapes of Oxfordshire, England to test the effect of IBD and IBB on toad genetic differentiation. We detected no significant effect of IBD (range 2–22 km between breeding ponds) on Common Toad genetic differentiation at this scale. We did, however, identify a significant and positive relationship between IBB and Common Toad genetic differentiation. Breeding populations were more genetically different with increasing barrier distance. The lack of a relationship between IBD and toad genetic differentiation could suggest that Common Toads are not as philopatric as previously thought, with reduced availability of suitable breeding ponds possibly driving more migrants to disperse greater distances and thereby possibly improving genetic mixing of the metapopulation.